The Tides of Teaching: Rising to New Levels of Understanding Through Negotiation and Conversation in an Online Reading Course (LEARNing Landscapes, 2013)
This study, conducted with eight elementary/ middle school teachers enrolled in an online reading course, asserts that through the development of relationships, the negotiation of a framework for study, and critical attention to generating and sustaining an environment conducive to learning, including interaction that promotes sincere conversation, that online learning can lead to substantial and meaningful professional insight. As a conceptual framework for this study I draw from images of the tides. Tides as metaphor provide me with a starting point for contemplation, an analogy from nature that, like teaching, has been an integral part of my life.
Keywords: elementary; middle school; reading course; online; realtionship; environment; negotiation; critical; learning; teacher